Weathering features of a remineralizer in soil under different land uses - Silva, Rafael Cipriano da (2022)
The objective of this work was to analyze the mineralogical, morphological, and compositional modifications resulting from the weathering of diabase grains buried into soil under different land uses for up to 378 days. Samples of comminuted diabase were put into polyester bags and buried into soil under corn crop, elephant grass, and woods, being unburied and evaluated after four time periods. The samples of the remineralizer (RM) were analyzed by X-ray diffractometry, total chemical analysis, scanning electron microscopy, and Al (Alo and Ald) and Fe (Fed and Feo) contents extracted by sodium dithionite-citrate-bicarbonate (DCB) and ammonium oxalate (AAO) solutions. Plagioclases and pyroxenes were the most weathered minerals in all three land uses and showed the same pattern of elemental gains and losses. The characterization of Fe and Al solubility in DCB and AAO showed that the greatest change in these elements was from the lithogenic and crystalline to the pedogenic and amorphous phase, when compared with their total content. Plagioclases and pyroxenes were the most weathered minerals, and Fe and Al show a great transfer from the crystalline to the amorphous phase, with values up to 26 and 175, respectively, for the ratios between bags with RM/Feo and RM-control and bags with RM/Alo and RM-control.